Fatal pneumonia following search and rescue operation - How, Soon Hin; Ramalingam, Rajalingam; Kuan, Yeh Chunn; Ahmad, Norazah; Ismail, Ahmad Izuanuddin; Iskandar , Bahari; Sapian, M. (Asian Pacifi c Society of Respirology, 2012)
Introduction On 26th June 2010, a young man was suspected to have drowned at Lubuk Yu, a natural recreational forest with river and waterfall in Pahang. A rescue team was formed, comprising of 150 members from police offi cers, army offi cers, divers, fi remen and volunteers from a nearby village. His body was recovered fi ve days later. Following this rescue operation, at least 22 people presented with an acute febrile illness. Objective To describe ten patients with melioidotic pneumonia. Results Six were culture-confi rmed for melioidosis only while four were positive for leptospirosis (based on polymerase chain reaction) and melioidosis. All except one had diabetes mellitus. Among these 10 patients, all had fever and cough, 8 had shortness of breath. Surprisingly, symptoms of myalgia, diarrhoea and vomiting were the presenting complaints in some of these patients. Chest radiograph showed bilateral consolidation in 6 and 7 patients died. Conclusions Melioidotic pneumonia in this series was associated with high mortality.